Mid-trimester resolution of marked dextroposition of the fetal heart preceding regression of extensive left fetal lung lesion consisting of hybrid congenital pulmonary airway malformation (CPAM) and bronchopulmonary sequestration (BPS) - David M. Sherer, MD; Ida Dhanuka, MD; Kayla Schacher, MD; Hubert Rodriguez-Tejada, MD; Aleksandra Zigalo, RDMS; Mila Kheyman, RDMS; Harry Zinn, MD; Fancisca T. Velcek, MD; Mudar Dalloul, MD (Radiology Case Reports)
Extensive congenital pulmonary airway malformation (CPAM) of the left fetal lung and associated marked dextroposition of the fetal heart were noted at 21 weeks’ gestation. The right fetal lung appeared compressed with the cardiomediastinal shift angle measuring approximately 20 degrees. Potential subsequent right pulmonary hypoplasia was considered. At 26 weeks’ gestation, despite the continued presence of extensive CPAM of the left fetal lung, spontaneous resolution of the dextroposition of the fetal heart was noted. Subsequent repeat ultrasound assessments confirmed gradual continued in-utero regression of the left lung lesion. The patient spontaneously delivered a vigorous infant neonate at 39 and 4/7 weeks’ gestation. Birth weight was 3175 grams, and following brief CPAP management for mild transient tachypnea of the newborn, and negative chest X-ray, the infant was discharged in good health on Day 2 of life. Neonatal CT angiography demonstrated CPAM of the left lower lobe. In addition, a feeding vessel was seen emanating directly from the thoracic aorta, indicating an intralobar brochopulmonary sequestration (BPS) component of the left lung lesion, consistent with a hybrid lung lesion (CPAM and intralobar BPS). At 2 months of life the infant underwent uneventful resection of the left lower lobe with pathology confirmation of the hybrid lung lesion. This case demonstrates that relatively rapid regression of severe cardiomediastinal shift associated with extensive hybrid lung lesions may occur. Our case indicates that spontaneous regression of marked cardiomediastinal shift appears to be a reassuring prognostic sign despite the continued presence of this lesion.